Revision of the genus Laophontodes T. Scott (Copepoda, Harpacticoida, Ancorabolidae), including the description of a new species and a key to species - Kai Horst George; Linda Maria Anne Lehmanski; Terue Cristina Kihara (ZooKeys, 2020)
The description of Laophontodes volkerlehmanskii sp. nov. (Copepoda, Harpacticoida, Laophontodinae Lang) from the deep sea of the Kairei Field, western Indian Ocean, prompted the examination of the phylogenetic status of Laophontodes T. Scott and the relationships within the genus. The allocation of L. volkerlehmanskii sp. nov. to Laophontodes based on diagnostic characters was relatively straightforward, yet phylogenetic analysis of the genus considering 39 morphological characters detected not a single autapomorphy. This indicates that Laophontodes, which seems to form a monophylum with Ancorabolina George and Bicorniphontodes George, Glatzel & Schröder, actually represents the stem-lineage, retaining the characters of the common ancestor without having developed unique derived morphological characters. Most of the 13 known species of Laophontodes can be characterised by distinct apomorphies. However, phylogenetic comparison highlights some uncertainties due to the apparent heterogeneous distribution of some derived characters across the species, the weakness of other features, and the fragmentary and inadequate description of several species, which, in combination with the unavailability of type material, prevents a detailed comparison of several phylogenetically relevant characters. Thus, the analysis presented here provides a further step towards understanding the systematic relationships of and within Laophontodes, rather than a conclusive answer. Nonetheless, a detailed character discussion and a key to species are given.